Reversion of malignant phenotypes of human glioblastoma cells by β-elemene through β-catenin-mediated regulation of stemness-, differentiation- and epithelial-to-mesenchymal transition-related molecules. Issue 1 (December 2015) - Zhu, Tingzhun; Li, Xiaoming; Luo, Lihan; Wang, Xiaogang; Li, Zhiqing; Xie, Peng; Gao, Xu; Song, Zhenquan; Su, Jingyuan; Liang, Guobiao
Abstract Background Glioblastoma is the most common and lethal type of primary brain tumor.β -Elemene, a natural plant drug extracted fromCurcuma wenyujin, has shown strong anti-tumor effects in various tumors with low toxicity. However, the effects ofβ -elemene on malignant phenotypes of human glioblastoma cells remain to be elucidated. Here we evaluated the effects ofβ -elemene on cell proliferation, survival, stemness, differentiation and the epithelial-to-mesenchymal transition (EMT) in vitro and in vivo, and investigated the mechanisms underlying these effects. Methods Human primary and U87 glioblastoma cells were treated withβ -elemene, cell viability was measured using a cell counting kit-8 assay, and treated cells were evaluated by flow cytometry. Western blot analysis was carried out to determine the expression levels of stemness markers, differentiation-related molecules and EMT-related effectors. Transwell assays were performed to further determine EMT of glioblastoma cells. To evaluate the effect ofβ -elemene on glioblastoma in vivo, we subcutaneously injected glioblastoma cells into the flank of nude mice and then intraperitoneally injected NaCl orβ -elemene. The tumor xenograft volumes were measured every 3 days and the expression of stemness-, differentiation- and EMT-related effectors was determined by Western blot assays in xenografts. Results β -Elemene inhibited proliferation, promoted apoptosis, impaired invasiveness in glioblastoma cells and suppressed the growth of animal xenografts. The expression levels of the stemness markers CD133 and ATP-binding cassette subfamily G member 2 as well as the mesenchymal markers N-cadherin andβ -catenin were significantly downregulated, whereas the expression levels of the differentiation-related effectors glial fibrillary acidic protein, Notch1, and sonic hedgehog as well as the epithelial marker E-cadherin were upregulated byβ -elemene in vitro and in vivo. Interestingly, the expression of vimentin was increased byβ -elemene in vitro; this result was opposite that for the in vivo procedure. Inhibitingβ -catenin enhanced the anti-proliferative, EMT-inhibitory and specific marker expression-regulatory effects ofβ -elemene. Conclusions β -Elemene reversed malignant phenotypes of human glioblastoma cells throughβ -catenin-involved regulation of stemness-, differentiation- and EMT-related molecules.β -Elemene represents a potentially valuable agent for glioblastoma therapy.